Random Periareolar Fine-Needle Aspiration: The New Pap Smear of the Breast? - Lester, Joanne (Harborside Press, 2012)
Random periareolar fine-needle aspiration continues to gain scientific credence in the short-term identification of women at increased risk for breast cancer. As this technique becomes more widely used, APs may seek to be trained in an effort to expand clinical trials, and someday provide a "Pap smear of the breast" for the women who need it most.